2017
DOI: 10.5114/jcb.2017.68469
|View full text |Cite
|
Sign up to set email alerts
|

Novel anesthetic technique for combined intracavitary and interstitial brachytherapy for cervix cancer in an outpatient setting

Abstract: PurposeTo determine the feasibility and safety of outpatient combined intracavitary and interstitial brachytherapy for cervix cancer with sedation and local anesthesia.Material and methodsWe included patients diagnosed with non-metastatic cervix cancer and have completed brachytherapy between December 2015 and December 2016. Moderate to deep sedation was achieved using intravenous midazolam, propofol, fentanyl, and oxycodone. Local anesthesia was achieved with 2% lignocaine gel and a paracervical block contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In this study, we found that the mean applicator insertion time and total procedural time was 32.4 ±14.9 minutes and 4.5 ±1.2 hours, respectively, which are comparable to results from other groups. Similar study by Leong and colleagues reported mean insertion time of 39 minutes and mean time to discharge of 4.1 hours [25]. Liu et al evaluated a technique of interstitial brachytherapy in 28 patients using applicator combining uterine tandem and metal needles, where the needles were inserted free-hand under real-time CT guidance [27].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, we found that the mean applicator insertion time and total procedural time was 32.4 ±14.9 minutes and 4.5 ±1.2 hours, respectively, which are comparable to results from other groups. Similar study by Leong and colleagues reported mean insertion time of 39 minutes and mean time to discharge of 4.1 hours [25]. Liu et al evaluated a technique of interstitial brachytherapy in 28 patients using applicator combining uterine tandem and metal needles, where the needles were inserted free-hand under real-time CT guidance [27].…”
Section: Discussionmentioning
confidence: 87%
“…So far, in existing publications on interstitial brachytherapy with modern hybrid applicators involving deep sedation, general, or spinal anesthesia, the procedures required the presence of anesthetist. Leong et al reported their experience of 35 insertions using Utrecht applicators performed under moderate to deep sedation administered by anesthetist, combining with paracervical block and local anesthesia [25]. A recent study by Walter et al presented their initial results of Venezia applicator in 10 patients, where insertions were performed under general or spinal anesthesia [18].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al in their study showed that local vaginal anaesthesia with 10% lidocaine solution can significantly decrease the degree of painful sensation during HDR-ICBT and is safe to administer for the procedure for cervical cancer [12]. Study done by Leong et al concluded that outpatient combined intracavitary and interstitial brachytherapy for cervix cancer with sedation and local anaesthesia is feasible and safe and could potentially lead to significant cost savings [13].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial applicable to BT found a significant pain reduction (13 mm vs 54 mm on pain visual analog scale) in patients undergoing laminaria placement, a procedure similar to dilation for BT, in which only mild uterine manipulation is anticipated ( 14 ). Despite the successful implementation of PCBs in several BT clinics internationally, adoption of brachytherapist-directed local anesthesia in the US has been limited ( [15] , [16] , [17] ).…”
Section: Methodsmentioning
confidence: 99%